2020
DOI: 10.1080/0092623x.2020.1748778
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Conflict Handling: Hand-Holding During and After Conflict Discussions Affects Heart Rate, Mood, and Observed Communication Behavior in Romantic Partners

Abstract: Improved conflict handling is important to reduce relational discord. Touch potentially has beneficial effects on three important characteristics of conflict discussions, i.e., physiological reactivity, affect and communication behavior. We studied effects of hand-holding between partners during conflict discussions (N ¼ 47 student couples) and after conflict discussions (N ¼ 53 student and N ¼ 45 clinical couples). During conflict discussions hand-holding caused lower heart rate reactivity, higher positive af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Affectionate touch is also particularly effective to buffer stress and to facilitate recovery from stress (Coan et al, 2006, 2017; Ditzen et al, 2007; Graff et al, 2019; Holt-Lunstad et al, 2008; Jakubiak & Feeney, 2016a, 2019; Robinson et al, 2015). For example, an imagined affectionate touch intervention buffered physical and social-evaluative stress (Jakubiak & Feeney, 2016a); hand-holding mitigated self-reported, observer-coded, and physiological stress during couple conflict discussions (Conradi et al, 2020; Jakubiak & Feeney, 2019); and a 6-week intervention to increase kissing, a particularly intimate form of affectionate touch, reduced perceived stress (Floyd et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Affectionate touch is also particularly effective to buffer stress and to facilitate recovery from stress (Coan et al, 2006, 2017; Ditzen et al, 2007; Graff et al, 2019; Holt-Lunstad et al, 2008; Jakubiak & Feeney, 2016a, 2019; Robinson et al, 2015). For example, an imagined affectionate touch intervention buffered physical and social-evaluative stress (Jakubiak & Feeney, 2016a); hand-holding mitigated self-reported, observer-coded, and physiological stress during couple conflict discussions (Conradi et al, 2020; Jakubiak & Feeney, 2019); and a 6-week intervention to increase kissing, a particularly intimate form of affectionate touch, reduced perceived stress (Floyd et al, 2009).…”
mentioning
confidence: 99%
“…For example, one recent diary study showed that receiving affectionate touch from one’s romantic partner predicted day-to-day increases in perceived partner responsiveness, closeness, relationship quality, and willingness to accommodate (Carmichael et al, 2021). Experimentally induced affectionate touch also enhances state security (i.e., feeling safe, cared for, and trusting) and cognitive interdependence (i.e., a sense of one-ness with one’s partner) (Jakubiak & Feeney, 2016b, 2019), promotes relationship intimacy in daily life (Durbin et al, 2021), and improves communication during conflict (Conradi et al, 2020; Jakubiak & Feeney, 2019).…”
mentioning
confidence: 99%
“…In still another study on handholding, 45 student couples held hands during conflict discussions (Conradi et al, 2020). Handholding during these discussions led to decreased heart rate and increased heart rate variability, suggesting a decrease in stress.…”
Section: Handholdingmentioning
confidence: 97%
“…Additionally, several studies showed that touch has a buffering effect on different stress reactions (e.g., Coan et al, 2017; Jakubiak & Feeney, 2016a). For example, when holding hands during a conflict discussion, partners showed less self-reported, observer-coded, and physiological stress (Conradi et al, 2020; Jakubiak & Feeney, 2019b). Ditzen et al (2019) demonstrated that spontaneous affectionate touch before and after a social stress induction (including giving a speech and computing a difficult arithmetical task in front of unexpressive judges) reduced cortisol reactivity and accelerated cortisol recovery.…”
Section: Introductionmentioning
confidence: 99%